Interpersonal Violence and Psychological Well-Being: Perspectives of Low-Income Patients, Social Workers, and Medical Doctors in Mexico City, Mexico - Zhen-Duan, Jenny (Journal of interpersonal violence, 2022)
The violence epidemic in Mexico is becoming more widespread. Using a social-ecological framework, the current study sought to understand interpersonal violence among those impoverished communities in Mexico City, Mexico. Participants were recruited from Community Health Centers located within districts that were densely populated, had high rates of poverty and marginalization, and where people experience complex social needs. Semi-structured interviews were conducted with patients, social workers, and medical doctors (N = 15) who were either receiving or providing services in these centers. Data were analyzed using an inductive, thematic approach. Analysis resulted in three themes: (a) interpersonal violence permeates all settings in which people live and interact; (b) social and cultural factors increase the risk of becoming a perpetrator or victim of interpersonal violence; and (c) interpersonal violence is closely intertwined with mental health. Rapid changes within gender roles and expectations in Mexico, combined with widening income inequality, are shifting dynamics within families that may be inherently linked to interpersonal violence. Our findings support the conceptualization of interpersonal violence at the four levels of the social-ecological framework: individual, relationship, community, and societal. Prevention and interventions for violence reduction must be applied across the four levels simultaneously. Community-level efforts should go toward strengthening existing community health centers and equipping primary care providers with training and resources on the screening and triaging of patients encountering interpersonal violence.